Modified boundary condition at Si-SiO2 interface for modeling of threshold voltage and subthreshold swing of short-channel SOI MESFET's - Jit S.; Pandey P.; Kumar A.; Gupta S.K. (My University, 2025)
A modified boundary condition at Si-SiO2 interface for modeling of threshold voltage and subthreshold swing of SOI MESFET were discussed. It was observed that the at the oxide side of the interface there must be some change in surface charge density due to the additional change in the electric field at the Si side of the interface. It was also observed that there must be an equal and opposite sheet charge density at the Si side of the interface to accomodate the change in the electric field in the oxide region. The result shows that a change in the electric field may induce a sheet charge densitu on the Si side of the interface contributing to the subthreshold current.